The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10735-010-9259-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of protein C inhibitor in mouse development

Abstract: Proteolysis of extracellular matrix is an important requirement for embryonic development and is instrumental in processes such as morphogenesis, angiogenesis, and cell migration. Efficient remodeling requires controlled spatio-temporal expression of both the proteases and their inhibitors. Protein C inhibitor (PCI) effectively blocks a range of serine proteases, and recently has been suggested to play a role in cell differentiation and angiogenesis. In this study, we mapped the expression pattern of PCI throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Sperm morphology analysis demonstrated that SERPINA5 could protect the percentages of intact acrosomes or morphologically normal spermatozoa, indicating that SERPINA5 improves the fertilisation ability of sperm. Previous studies have shown that the binding of SERPINA5 to sperm acrosin precursor inhibits its activity, thus reducing the probability of sperm binding to oocytes [19,30,31]. Our study found that addition of low concentration of recombinant mouse SERPINA5 protein to HTF medium can promote the fertilisation ability of mouse sperm, but the high concentration of SERPINA5 protein inhibits the fertilisation ability of sperm.…”
Section: Discussionsupporting
confidence: 46%
“…Sperm morphology analysis demonstrated that SERPINA5 could protect the percentages of intact acrosomes or morphologically normal spermatozoa, indicating that SERPINA5 improves the fertilisation ability of sperm. Previous studies have shown that the binding of SERPINA5 to sperm acrosin precursor inhibits its activity, thus reducing the probability of sperm binding to oocytes [19,30,31]. Our study found that addition of low concentration of recombinant mouse SERPINA5 protein to HTF medium can promote the fertilisation ability of mouse sperm, but the high concentration of SERPINA5 protein inhibits the fertilisation ability of sperm.…”
Section: Discussionsupporting
confidence: 46%
“…Prior work has documented that fga, fgb, and fgg encoding fibrinogen alpha, beta and gamma chains in zebrafish, respectively, are homologous to human fibrinogen gene sequences (Vo et al, 2013). Moreover, protein C inhibitor (SERPINA5) is also a vital factor during hemostasis that can inhibit some coagulation factors, such as prothrombin and factor Xa (Wagenaar et al, 2010). The three treatments (0.7 µm MPs, Cu-NPs + 0.7 µm MPs and Cu-NPs + 7 µm MPs) resulted in the down-regulation of serpina7, an important component of SERPINA5, which weakened inhibitory effect on coagulation factors and reduced the feedback regulation of the coagulation process, indicating that the coagulation function of the organism has been activated.…”
Section: Hemostasismentioning
confidence: 99%
“…[30][31][32] A recent study determined the expression pattern of PCI during mouse development. 33 Widespread expression was detected in skin, brain ventricles, heart, skeletal muscles, urogenital tract, and cartilages. Strikingly, a strong and stagedependent PCI expression was observed in the developing lung, which may suggest that PCI is involved in lung morphogenesis and angiogenesis.…”
Section: Tissue Expression Of Protein C Inhibitormentioning
confidence: 99%
“…Strikingly, a strong and stagedependent PCI expression was observed in the developing lung, which may suggest that PCI is involved in lung morphogenesis and angiogenesis. 33 Because PCI has been suggested to play a role in tissue repair and regeneration by its inhibitory action on the activator of the hepatocyte growth factor, 34 the widespread expression during development could indicate that PCI is also important in cellular processes such as growth signaling.…”
Section: Tissue Expression Of Protein C Inhibitormentioning
confidence: 99%